MATHEMATICS SOFTSKILL: THE LEVEL OF MATHEMATICS PRE-SERVICE TEACHER STUDENT IN PROBLEM SOLVING - Palupi Sri Wijayanti; Esti Setiawati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
The ability to solve math problems is included in mathematics learning, so it needs to be emphasized as the achievement of mathematics learning competencies. This study aimed to determine the category of the level of students' mathematical problem-solving skills when learn using e-learning. This research is a quantitative descriptive study. The primary data source was obtained from the test scores of mathematics problem-solving ability of 7th-grade students of SMP N 3 Jetis (Junior high School). The research stages were carried out in three steps: preparation, implementation, and end—data analysis techniques used in the descriptive analysis to categorize students' mathematical problem-solving abilities. This study indicates that the category of students' problem-solving skills on mathematical tests in online learning is included in the category of sufficient. For the indicator of identify the elements identified, asked, and the adequacy of the required details is very high. Then, the aspect of formulating mathematical problems or compiling mathematical models is high, furthermore, for hands implementing strategies to solve problems, low for indicators explaining or interpreting the results of problem-solving.